Emerging and re-emerging zoonotic viral diseases in Southeast Asia: One Health challenge - Saba Villarroel, Paola Mariela; Gumpangseth, Nuttamonpat; Songhong, Thanaphon; Yainoy, Sakda; Monteil, Arnaud; Leaungwutiwong, Pornsawan; Missé, Dorothée; Wichit, Sineewanlaya (Frontiers in Public Health, 2023)
Southeast Asia (SEA) is undergoing social, environmental, and economic changes, and is among the most vulnerable to emerging and reemerging zoonotic viral diseases. In the last century, SEA has faced major viral outbreaks with great health and economic impact, including Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), arboviruses, highly pathogenic avian influenza (H5N1), and Severe Acute Respiratory Syndrome (SARS-CoV); and so far, imported cases of Middle East Respiratory Syndrome Coronavirus (MERS-CoV). Given the recent challenging experiences in addressing emerging zoonotic diseases, it is necessary to redouble efforts to effectively implement the “One Health” initiative in the region, which aims to strengthen the human-animal-plant-environment interface to better prevent, detect and respond to health threats by promoting sustainable development. This review provides an overview of important emerging and re-emerging zoonotic viral diseases in SEA, with emphasis on the main drivers, the epidemiological situation between January 2000 and October 2022, and the importance of One Health, to promote improved intervention strategies.